2000
DOI: 10.1128/jvi.74.9.3975-3983.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Viral Nucleocapsid Protein of Transmissible Gastroenteritis Coronavirus (TGEV) Is Cleaved by Caspase-6 and -7 during TGEV-Induced Apoptosis

Abstract: The transmissible gastroenteritis coronavirus (TGEV), like many other viruses, exerts much of its cytopathic effect through the induction of apoptosis of its host cell. Apoptosis is coordinated by a family of cysteine proteases, called caspases, that are activated during apoptosis and participate in dismantling the cell by cleaving key structural and regulatory proteins. We have explored the caspase activation events that are initiated upon infection of the human rectal tumor cell line HRT18 with TGEV. We show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
72
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 46 publications
9
72
0
Order By: Relevance
“…It has been demonstrated that host cell caspases, which are activated during coronavirus infection, are responsible for this cleavage (31). A common caspase cleavage motif is present in all of the mentioned coronavirus N proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that host cell caspases, which are activated during coronavirus infection, are responsible for this cleavage (31). A common caspase cleavage motif is present in all of the mentioned coronavirus N proteins.…”
Section: Discussionmentioning
confidence: 99%
“…During transmissible gastroenteritis coronavirus infection, caspase activation causes cleavage of the viral nucleocapsid protein (26). During infection with influenza, virus cleavage of the nucleocapsid protein has been observed during the process of apoptosis in late stages of the infection, and the primary structure of NP of human influenza viruses (A and B) has been shown to have proteolytic sites, which engage involvement of caspases (27).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, however, it is now well recognized that caspase-mediated cleavage of many viral proteins is a direct requirement for propagation of those viruses (10). Specifically, caspase 2 has been implicated in the cleavage of FCV capsid (14), whereas caspase 6 was found to be involved in the processing of human astrovirus HAstV capsid precursor (12), in TGEV nucleocapsid cleavage (11), and in HIV-induced apoptosis of T lymphocytes (103). Inasmuch as limited cleavage of proteins can either lead to the functional inhibition or activation of these proteins (104 -105) we could hypothesize that caspase-mediated cleavage of the NS5A protein may modulate the multiple functions of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Several caspases have been shown to target the structural proteins of different viruses, including transmissible gastroenteritis coronavirus (TGEV) (11), human astrovirus (HAstv) (12), influenza A virus (13), and feline calicivirus (FCV) (14), as well as nonstructural viral proteins, such as the NS1 from the Aleutian mink disease parvovirus (ADV) (15), the adenovirus (Ad) E1A (16), or the immediately early protein 22 from herpes simplex virus (HSV-1) (17), with an impact on viral pathogenesis. Interestingly, caspase 3, the executioner caspase that targets the majority of cellular substrates during apoptosis, is also responsible for cleaving many viral proteins, and numerous studies have implicated caspase 6, 7, and 2 in the cleavage of different viral protein substrates (11,14,16). Because most viruses encode inhibitors of caspases to evade cellular antiviral mechanisms that lead cells to apoptosis, (18 -21) it is not immediately apparent why viruses rely on caspases for cleavage of their own proteins.…”
mentioning
confidence: 99%